Development of E-Modules based on Contextual Teaching and Learning (CTL) on the actualization of Pancasila values - Riyana Riyana; Didik Sukriono; Sri Untari (Himpunan Pengembang Kurikulum Indonesia, 2025)
The teaching of Pancasila Education in this school faces challenges in applying Pancasila values practically and relevantly to students' lives, thus requiring an effective and innovative learning approach. The main objective of this research is to design an e-module that integrates CTL concepts with the material to actualize Pancasila values and test the effectiveness of using the e-module. This research uses the Research and Development method with the ADDIE model approach (Analysis, Design, Development, Implementation, and Evaluation). The researcher conducted a needs analysis to determine students' skills and knowledge about Pancasila's values. Then, the e-module design was carried out by considering CTL principles and integrating multimedia elements, such as text, images, audio, and video. The developed e-module was tested on students, and its effectiveness was measured through pre-tests and post-tests to determine the improvement in learning outcomes. The research results show that CTL-based e-modules can improve students' learning outcomes, especially in cognitive and affective aspects. The results of the development of the CTL-based e-module show that the e-module is capable of presenting learning materials engagingly and interactively, as well as facilitating students in applying the values of Pancasila in their daily lives. Interactive features, such as quizzes, simulations, and context-based discussions, help increase students' active participation in learning. Abstrak Pembelajaran Pendidikan Pancasila di sekolah ini dihadapkan pada tantangan dalam menerapkan nilai-nilai Pancasila secara praktis dan relevan bagi kehidupan peserta didik, sehingga diperlukan pendekatan pembelajaran yang efektif dan inovatif. Tujuan utama penelitian ini adalah untuk merancang e-modul yang memadukan konsep-konsep dari CTL dengan materi aktualisasi nilai-nilai Pancasila, serta menguji efektivitas penggunaan e-modul tersebut. Penelitian ini menggunakan metode pengembangan (Research and Development) dengan pendekatan model Analysis, Design, Development, Implementation, and Evaluation (ADDIE). Peneliti melakukan analisis kebutuhan untuk mengetahui keterampilan dan pengetahuan peserta didik tentang nilai-nilai Pancasila. Kemudian desain e-modul dilakukan dengan memperhatikan prinsip-prinsip CTL dan mengintegrasikan elemen multimedia, seperti teks, gambar, audio, dan video. E-modul yang dikembangkan diuji coba pada peserta didik, dan efektivitasnya diukur melalui pre-test dan post-test untuk mengetahui peningkatan hasil belajar. Hasil penelitian menunjukkan bahwa penggunaan e-modul berbasis CTL dapat meningkatkan hasil belajar peserta didik, terutama dalam aspek kognitif dan afektif. Hasil pengembangan e-modul berbasis CTL menunjukkan bahwa e-modul tersebut mampu menyajikan materi pembelajaran secara menarik dan interaktif, serta memfasilitasi peserta didik dalam mengaplikasikan nilai-nilai Pancasila dalam kehidupan sehari-hari. Fitur-fitur interaktif, seperti kuis, simulasi, dan diskusi berbasis konteks, membantu meningkatkan partisipasi aktif peserta didik dalam pembelajaran. Kata Kunci: contextual teaching and learning; e-modul; hasil belajar; nilai-nilai Pancasila; pendidikan Pancasila